A review of University Education in North and South America - Dorin, Michael (2017)
North America and South America have a large number of universities, and each university has its owns functions and missions. It has been 18 years since the World Conference on Higher Education (United Nations Educational, Scientific and Cultural Organization - UNESCO, 1998). At that conference, UNESCO analyzed the situation of higher education and stated changes that needed to be made in the university sphere of the 21st century. Examples of these changes include calls for better access to education; a greater variety of teaching styles; and more research and exchange of researches’ results. This document focuses on the details and realities of these changes. This publication also examines how universities in the North (focus in the United States) and South America differ in these implementations.